Uso de áreas agrícolas por Mazama gouazoubira (Mammalia, Cervidae) no Estado de São Paulo - Rodrigues, Thiago F. [UNESP]; Cerveira, Josi F. [UNESP]; Duarte, José M. B. [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2014)
Brown brocket deer (Mazama gouazoubira, Fischer 1814) is a species with widespread distribution in different biomes in Brazil, however little is known about habitat use in landscapes with high presence of agriculture. This research project aims to analyze the preference of habitat used by brown brocket deer in an agrosystem dedicated to production of sugarcane. Our study was carried out in northeaster portion of state of Sao Paulo in municipality of Jaboticabal at Santa Cecília farm. Our study area has about 185 ha with different formations which were classified as (i) adult sugarcane (1-3 m height), (ii) young sugarcane (up to 1m) and without sugarcane (post crop), (iii) eucalyptus and (iv) remnant native vegetation. We actively searched for signs (footprint) or visualizations in unpaved roads among cultivated plots and in perimeter of study area. Sampling was carried out monthly during two consecutive days between February 2011 and January 2012 with total effort of 204 km. Geographic coordinates and type of the surrounding vegetation was obtained for each record. Considering the rotation of annual crops, the total availability was estimated for each vegetation formation throughout the sampling period. Our results (forty four records) show that brown brocket deer avoids use open areas (young sugarcane and without sugarcane) and preferred environments near to native forests and eucalyptus. It is known that brown brocket deer presents great ecological plasticity, however the species prefers environments pervaded by remnants of native or regenerating forest, suggesting a mosaic as found in the present project can sustain populations of the species.

O veado-catingueiro, Mazama gouazoubira (Fischer, 1814) é a espécie mais abundante de cervídeo do Brasil e suas populações têm resistido a alterações antrópicas consideráveis e ocupam regularmente áreas modificadas. Pouco se sabe sobre o uso de ambientes agrícolas pela espécie, portanto, este trabalho teve por objetivo analisar a preferência de uso do hábitat por M. gouazoubira em um agrossistema dedicado à produção de cana-de-açúcar. O trabalho foi desenvolvido na Fazenda Santa Cecília, município de Jaboticabal, região nordeste do estado de São Paulo, entre fevereiro de 2011 e janeiro de 2012. A área de estudo abrange cerca de 185 ha, cujas formações podem ser classificadas em plantios de cana-de-açúcar nos estágios (i) adulto (1 a 3 m altura), (ii) jovem (até 1 m) e sem cana (pós-safra), além de (iii) eucalipto e (iv) remanescentes de mata ciliar. Os registros foram obtidos percorrendo-se a pé os aceiros entre os talhões cultivados e o perímetro da área, totalizando 204 km percorridos em busca de pegadas e visualizações. A amostragem foi realizada mensalmente, com duração de dois dias consecutivos, entre 6h e 9h, e para cada registro obteve-se a coordenada geográfica e o tipo de vegetação do entorno. Considerando a rotatividade das culturas anuais, foi estimada a disponibilidade total, em hectares, de cada formação vegetacional ao longo do período de amostragem. Foram obtidos 44 registros, sendo que M. gouazoubira evitou o uso das áreas com cana jovem e sem cana e preferiu ambientes próximos à mata ciliar e aos plantios de eucalipto. Estes resultados sugerem que, embora M. gouazoubira apresente grande plasticidade ecológica, existe preferência por ambientes florestais, sugerindo que um mosaico como o encontrado no presente projeto pode sustentar populações da espécie.
Use of agricultural areas by Mazama gouazoubira (Mammalia, Cervidae) in state of São Paulo
Keywords: Brown brocket deer; Footprints; Use and habitat selection; Veado-catingueiro; Pegadas; Uso e seleção do hábitat